Knowledge of danger signs in pregnancy and their associated factors among pregnant women in Hosanna Town, Hadiya Zone, southern Ethiopia - Mesele, Tiruye Tilahun; Syuom, Asmra Tesfahun; Molla, Eshetie Amare (Frontiers in Reproductive Health, 2023)
Abstract Background: Pregnancy danger signs are unexpected symptoms that can lead to maternal health complications which occur during pregnancy. The sub-Saharan Africa countries including Ethiopia maternal death is high. Little is known about knowledge of danger signs during pregnancy and its associated factors in community level. Methods: Community based cross-sectional study was conducted to assess of knowledge about obstetric danger signs among pregnant women in Hosanna Zuria Kebeles from June 30- July 30/2021. Simple random sampling method was used to select those eligible pregnant women. The sample size was proportionally allocated based on the number of pregnant women in each Kebele. Data was collected by face to face interview using a pretested questionnaire. The descriptive result was presented in proportion whereas the analytic part was presented with an adjusted odds ratio. Results: Prevalence of good knowledge on pregnancy danger signs was 259(63.2 %, 95%CI: [58.3, 67.8]).The most commonly known danger signs during pregnancy were severe vaginal bleeding 227(55.4%) followed by Blurred vision 224 (54.6%). In multivariable analysis, Age of respondent (AOR=3.29:95%CI [1.15, 9.38]), tertiary education of mother (AOR=5.40:95%CI [2.56, 11.34]) and number of living birth (AOR=3.95:95% CI [2.08, 7.48]) were statically significant factors associated with good knowledge on danger signs of pregnancy. Conclusion and Recommendation: There was a low prevalence of knowledge of pregnancy danger signs among pregnant mother. Maternal advanced age, respondent’s education status and number of living birth were found to have independent determining factors for level of knowledge on pregnancy danger signs among pregnant mother. Better to focus on appropriate information dissemination based on the standard about danger signs of pregnancy in each health facility. Ministry of health should be strengthening reproductive health services in rural areas to get quality antenatal care follow up by designing an appropriate strategies including provision of targeted information to advanced age mothers. Further study needs to be conducted by including danger signs during pregnancy, childbirth and post natal periods at community level for better generalization. Key Words: Danger Signs, Hadiya Zone, Knowledge, Ethiopia, Pregnancy